Anti-efflorescence concrete and preparation method thereof
By adding boric acid, activated carbon, microsilicon powder and nanosilica to the anti-panol concrete, the problems of unstable and high cost of anti-panol effect in the prior art are solved, and the efficient and low-cost anti-panol effect is achieved, and the overall performance of the concrete is improved.
Patent Information
- Application Number
- CN202510170862.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-04-15
AI Technical Summary
Existing anti-pan-alkali concretes have high costs when achieving stable effects and may cause secondary damage to the concrete when the pan-alkali surface has been repaired.
By adding boric acid, activated carbon, microsilicon powder and nanosilicon dioxide to the concrete, the adsorption, reaction and filling effects of these materials can be used to reduce the occurrence of alkaline and improve the mechanical properties and compactness of the concrete.
It has achieved the reduction of the occurrence of alkaline-spreading phenomenon in concrete, improved the compressive strength and long-term stability of concrete, and at the same time reduced the treatment cost and avoided secondary damage to concrete.
Smart Images

Figure BDA0005273988700000081 
Figure BDA0005273988700000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to an anti-efflorescence concrete and a preparation method thereof. Background Art
[0002] As an important innovation in the field of building materials, anti-efflorescence concrete aims to solve the efflorescence problem that traditional concrete is prone to during use. Efflorescence, the white salt frost that appears on the surface of concrete, is mainly formed by soluble salt substances in the concrete migrating to the surface with water and evaporating to the surface. It not only affects the appearance of concrete, but also may weaken its structural strength and durability.
[0003] At present, the research and development and application of anti-efflorescence concrete have made certain progress. For example, by optimizing the concrete formula, selecting low-alkali cement, controlling water consumption, adding anti-efflorescence admixtures, etc., the content of soluble alkali in concrete has been effectively reduced, reducing the occurrence of efflorescence. At the same time, improving the construction process, such as strengthening vibration and extending the curing time, further improves the anti-efflorescence performance of concrete.
[0004] However, there are still some problems and challenges in the existing anti-efflorescence concrete. On the one hand, due to the diversity and regional differences of concrete raw materials, as well as the uncertainty of the construction environment, it is difficult to achieve completely consistent anti-efflorescence effects, and the efflorescence problem is still prominent in some regions or under specific conditions. On the other hand, although there are a variety of anti-efflorescence measures, the treatment cost is high, and when repairing the concrete surface that has already experienced efflorescence, it may cause secondary damage to the concrete itself, affecting the overall performance.
[0005] Therefore, how to provide an anti-efflorescence alkali concrete with stable performance and low cost is a technical problem that technical personnel in this field need to solve urgently. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes an anti-efflorescence concrete and a preparation method thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] An anti-efflorescence concrete comprises the following raw materials in parts by weight:
[0009] 50-70 parts of cementitious material, 30-40 parts of coarse aggregate, 35-45 parts of fine aggregate, 5-8 parts of water reducer, 2-5 parts of boric acid, 10-15 parts of activated carbon, 5-8 parts of microsilica powder and 1-5 parts of nano silicon dioxide.
[0010] Beneficial effects: The boric acid, activated carbon, microsilica and nano-silica in the present invention can reduce the occurrence of efflorescence by adsorbing alkaline substances, improving the compactness of concrete, consuming alkaline substances and enhancing the mechanical properties of concrete. First, the boric acid in the present invention has weak acidity, which can reduce the alkalinity of the concrete surface, thereby alleviating the efflorescence phenomenon to a certain extent, and at the same time can promote the hydration reaction of cement, and improve the early strength and long-term stability of concrete. Secondly, the activated carbon in the present invention can adsorb alkaline substances that penetrate the surface of concrete or mortar, thereby reducing the occurrence of efflorescence. In addition, the addition of activated carbon can also improve the microstructure of concrete, improve its compactness and impermeability, thereby further reducing the precipitation of alkaline substances. In addition, the microsilica in the present invention can react with alkaline substances in concrete to generate low-alkalinity hydrated calcium silicate gel, thereby reducing the alkalinity of concrete. The addition of microsilica can also fill the pores in concrete, improve the compactness and impermeability of concrete, thereby reducing the precipitation of alkaline substances. At the same time, the nano-silicon dioxide of the present invention can promote the early hydration of cement and consume the excess alkali substances in the concrete pore solution to form gel. The formation of gel reduces the porosity of concrete and improves the pore structure, thereby blocking the transport path of free water and free alkali, and effectively inhibiting the efflorescence phenomenon. The boric acid, activated carbon, microsilica and nano-silicon dioxide in the present invention also have a certain synergistic effect, which jointly improves the anti-efflorescence effect of concrete.
[0011] Preferably, the gelling material comprises the following raw materials in parts by weight:
[0012] 40-55 parts of cement, 10-25 parts of fly ash, 10-25 parts of slag powder and 1-2 parts of gypsum.
[0013] Preferably, the cement is Portland cement.
[0014] The fly ash is Class I fly ash with a density of no more than 2600 kg / m 3 .
[0015] Preferably, the gypsum is dihydrate desulfurized gypsum and / or dihydrate dephosphorized gypsum.
[0016] Beneficial effects: The dihydrate gypsum in the present invention can react with other cementitious materials to generate ettringite and calcium silicate hydrate gel, which are mutually gelled to form a whole with a certain strength.
[0017] Preferably, the coarse aggregate comprises ceramsite.
[0018] The particle size of the coarse aggregate is 5mm-20mm.
[0019] Preferably, the fine aggregate includes rubber particles, quartz sand and basalt machine-made sand.
[0020] The particle size of fine aggregate is 0.15mm-2.36mm, and the fineness modulus is 2.3-2.5.
[0021] More preferably, the rubber particles are obtained by treating waste rubber with an alkali solution, which specifically comprises the following steps:
[0022] The waste rubber is soaked in a NaOH solution with a mass concentration of 1-2% for 1 hour, and then crushed after drying to obtain the rubber particles.
[0023] Beneficial effects: The rubber particles in the present invention can improve the bonding tightness between aggregate and cementitious material, can maximize the advantages of aggregate and rubber particles, and improve the strength and toughness of concrete.
[0024] Preferably, the water reducer is a polycarboxylate water reducer.
[0025] A method for preparing alkali-resistant concrete comprises the following steps:
[0026] The cementitious material, coarse aggregate, fine aggregate, microsilica powder and nano-silicon dioxide are uniformly mixed to obtain a mixture, and then a water reducer and boric acid are dissolved and dispersed in water, mixed evenly with the mixture, vibrated and compacted, and cured at room temperature to obtain the anti-efflorescence alkali concrete.
[0027] Preferably, the mass ratio of water to gelling material is (1-2):(3-4).
[0028] Compared with the prior art, the present invention has the following advantages and technical effects:
[0029] The present invention provides an anti-efflorescence concrete and a preparation method thereof. The anti-efflorescence performance of the concrete is improved by adding boric acid, activated carbon, microsilica powder and nano-silica. In addition, boric acid and nano-silica can promote cement hydration reaction and improve the strength of concrete; activated carbon can adsorb harmful substances and slow down the aging speed of concrete; microsilica powder and nano-silica both have a filling effect and volcanic ash activity, can fill pores, and improve the compactness and impermeability of concrete. These synergistic effects significantly improve the overall performance of concrete and greatly reduce the occurrence of efflorescence in concrete. Finally, the raw materials provided by the present invention are easy to obtain, the preparation method is simple, and it is conducive to promotion and application. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.
[0032] The embodiment of the present invention provides an anti-efflorescence concrete, comprising the following raw materials in parts by weight:
[0033] 50-70 parts of cementitious material, 30-40 parts of coarse aggregate, 35-45 parts of fine aggregate, 5-8 parts of water reducer, 2-5 parts of boric acid, 10-15 parts of activated carbon, 5-8 parts of microsilica powder and 1-5 parts of nano silicon dioxide.
[0034] In a preferred embodiment, the gelling material comprises the following raw materials in parts by weight:
[0035] 40-55 parts of cement, 10-25 parts of fly ash, 10-25 parts of slag powder and 1-2 parts of gypsum.
[0036] In a preferred embodiment, the cement is Portland cement.
[0037] The fly ash is Class I fly ash with a density of no more than 2600 kg / m 3 .
[0038] In a preferred embodiment, the gypsum is dihydrate desulfurized gypsum and / or dihydrate dephosphorized gypsum.
[0039] In a preferred embodiment, the coarse aggregate comprises ceramsite.
[0040] The particle size of the coarse aggregate is 5mm-20mm.
[0041] In a preferred embodiment, the fine aggregate includes rubber particles, quartz sand and basalt machine-made sand.
[0042] The particle size of fine aggregate is 0.15mm-2.36mm, and the fineness modulus is 2.3-2.5.
[0043] In a more preferred embodiment, the rubber particles are obtained by treating waste rubber with an alkali solution, and specifically include the following steps:
[0044] The waste rubber is soaked in a NaOH solution with a mass concentration of 1-2% for 1 hour, and then crushed after drying to obtain the rubber particles.
[0045] In a preferred embodiment, the water reducer is a polycarboxylate water reducer.
[0046] The embodiment of the present invention also provides a method for preparing alkali-resistant concrete, comprising the following steps:
[0047] The cementitious material, coarse aggregate, fine aggregate, microsilica powder and nano-silicon dioxide are uniformly mixed to obtain a mixture, and then a water reducer and boric acid are dissolved and dispersed in water, mixed evenly with the mixture, vibrated and compacted, and cured at room temperature to obtain the anti-efflorescence alkali concrete.
[0048] In a preferred embodiment, the mass ratio of water to gelling material is (1-2):(3-4).
[0049] Unless otherwise specified, the cement in the embodiments of the present invention is PO42.5 silicate cement;
[0050] The fly ash is Class I fly ash, with a density not exceeding 2600kg / m 3 ;
[0051] The activated carbon is corn straw activated carbon;
[0052] The coarse aggregate is ceramsite with a particle size of 5mm-20mm;
[0053] The particle size of fine aggregate is 0.15mm-2.36mm, and the fineness modulus is 2.3-2.5.
[0054] The rubber particles are obtained by treating waste rubber with an alkaline solution, and specifically include the following steps:
[0055] The waste rubber is soaked in a NaOH solution with a mass concentration of 1-2% for 1 hour, and then crushed after drying to obtain the rubber particles.
[0056] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0057] Example 1
[0058] An anti-efflorescence concrete comprises the following raw materials in parts by weight:
[0059] 60 parts of cementitious material, 35 parts of coarse aggregate, 40 parts of fine aggregate (rubber particles and quartz sand mixed in a mass ratio of 1:5), 6 parts of polycarboxylic acid water reducer, 4 parts of boric acid, 13 parts of activated carbon, 6 parts of microsilica powder and 3 parts of nano silicon dioxide.
[0060] Wherein, the gelling material comprises the following raw materials in parts by weight:
[0061] 48 parts of cement, 17 parts of fly ash, 20 parts of slag powder and 2 parts of desulfurized gypsum dihydrate.
[0062] A method for preparing alkali-resistant concrete comprises the following steps:
[0063] The cementitious material, coarse aggregate, fine aggregate, microsilica powder and nano silicon dioxide are mixed evenly to obtain a mixture, and then a water reducer and boric acid are dissolved and dispersed in water, and then mixed evenly with the mixture, wherein the mass ratio of water to cementitious material is 1:3. After vibration pressing and room temperature curing, the anti-efflorescence alkali concrete is obtained.
[0064] Example 2
[0065] An anti-efflorescence concrete comprises the following raw materials in parts by weight:
[0066] 50 parts of cementitious materials, 30 parts of coarse aggregate, 45 parts of fine aggregate (rubber particles and basalt machine-made sand are mixed in a mass ratio of 1:5), 5 parts of polycarboxylic acid water reducer, 2 parts of boric acid, 15 parts of activated carbon, 5 parts of microsilica powder and 1 part of nano silicon dioxide.
[0067] Wherein, the gelling material comprises the following raw materials in parts by weight:
[0068] 55 parts of cement, 10 parts of fly ash, 10 parts of slag powder and 2 parts of dephosphorized gypsum dihydrate.
[0069] A method for preparing alkali-resistant concrete comprises the following steps:
[0070] The cementitious material, coarse aggregate, fine aggregate, microsilica powder and nano silicon dioxide are mixed evenly to obtain a mixture, and then a water reducer and boric acid are dissolved and dispersed in water, and then mixed evenly with the mixture, wherein the mass ratio of water to cementitious material is 2:4. After vibration pressing and room temperature curing, the anti-efflorescence alkali concrete is obtained.
[0071] Example 3
[0072] An anti-efflorescence concrete comprises the following raw materials in parts by weight:
[0073] 70 parts of cementitious materials, 40 parts of coarse aggregate, 35 parts of fine aggregate (rubber particles, quartz sand and basalt machine-made sand mixed in a mass ratio of 1:3:3), 8 parts of polycarboxylic acid water reducer, 5 parts of boric acid, 15 parts of activated carbon, 8 parts of microsilica powder and 5 parts of nano silicon dioxide.
[0074] Wherein, the gelling material comprises the following raw materials in parts by weight:
[0075] 40 parts of cement, 25 parts of fly ash, 25 parts of slag powder and 1 part of desulfurized gypsum dihydrate.
[0076] A method for preparing alkali-resistant concrete comprises the following steps:
[0077] The cementitious material, coarse aggregate, fine aggregate, microsilica powder and nano silicon dioxide are mixed evenly to obtain a mixture, and then a water reducer and boric acid are dissolved and dispersed in water, and then mixed evenly with the mixture, wherein the mass ratio of water to cementitious material is 1:4. After vibration pressing and room temperature curing, the anti-efflorescence alkali concrete is obtained.
[0078] Comparative Example 1
[0079] The alkali-resistant concrete is different from the embodiment 1 only in that boric acid is not included. Other raw materials, process steps and parameters are the same as those of the embodiment 1.
[0080] Comparative Example 2
[0081] The alkali-resistant concrete is different from the embodiment 1 only in that the activated carbon is not included. Other raw materials, process steps and parameters are the same as those of the embodiment 1.
[0082] Comparative Example 3
[0083] A kind of alkali-resistant concrete, which is different from Example 1 only in that it does not include microsilica powder. Other raw materials, process steps and parameters are the same as those in Example 1.
[0084] Comparative Example 4
[0085] The alkali-resistant concrete is different from the embodiment 1 only in that nano-silicon dioxide is not included. Other raw materials, process steps and parameters are the same as those of the embodiment 1.
[0086] Comparative Example 5
[0087] The alkali-resistant concrete is different from the embodiment 1 only in that it does not include boric acid, activated carbon, microsilica powder and nano silicon dioxide. Other raw materials, process steps and parameters are the same as those of the embodiment 1.
[0088] Technical Effects
[0089] In order to verify the performance of the anti-efflorescence permeable concrete prepared by the present invention, 100mm×100mm×100mm anti-efflorescence permeable concrete plates were prepared according to Examples 1 to 3 and Comparative Examples 1-5, respectively, and polished after curing to 28 days. The compressive strength of the concrete was tested according to GB / T50081-2016 "Test Method for Mechanical Properties of Ordinary Concrete" (two groups of each sample were formed, 3 parallel samples in each group, and the average value of each group was taken); the chloride ion diffusion coefficient was tested according to GB / T50082-2009 "Test Method for Long-term Performance and Durability of Ordinary Concrete"; the ICP test method was used to test the calcium ion concentration in the anti-efflorescence permeable concrete solution to evaluate the efflorescence value of the permeable concrete. The measurement results are shown in Table 1:
[0090] Table 1
[0091]
[0092]
[0093] It can be seen from Table 1 that the boric acid, activated carbon, microsilica and nano-silica in the present invention can respectively improve the porosity, mechanical properties, impermeability and anti-alkali performance of concrete, and there is a certain synergistic effect between the several raw materials. The test results of Example 1 of the present invention are better than the sum of the effects of using the several raw materials alone.
[0094] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. An anti-efflorescence concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of cementitious material, 30-40 parts of coarse aggregate, 35-45 parts of fine aggregate, 5-8 parts of water reducer, 2-5 parts of boric acid, 10-15 parts of activated carbon, 5-8 parts of microsilica powder and 1-5 parts of nano silicon dioxide.
2. The alkali-resistant concrete according to claim 1, characterized in that: The gelling material comprises the following raw materials in parts by weight: 40-55 parts of cement, 10-25 parts of fly ash, 10-25 parts of slag powder and 1-2 parts of gypsum.
3. The anti-efflorescence concrete according to claim 2, characterized in that: The cement is silicate cement.
4. The anti-efflorescence concrete according to claim 2, characterized in that: The gypsum is dihydrate desulfurized gypsum and / or dihydrate dephosphorized gypsum.
5. The anti-efflorescence concrete according to claim 1, characterized in that: The coarse aggregate includes ceramsite.
6. The anti-efflorescence concrete according to claim 1, characterized in that: The fine aggregate includes one or any combination of rubber particles, quartz sand and basalt machine-made sand.
7. The anti-efflorescence concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.
8. The method for preparing alkali-resistant concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: The cementitious material, coarse aggregate, fine aggregate, microsilica powder and nano-silicon dioxide are mixed evenly to obtain a mixture, and then a water reducer and boric acid are dissolved and dispersed in water, and then mixed evenly with the mixture, and after vibration pressing and curing at room temperature, the anti-efflorescence alkali concrete is obtained.
9. The method for preparing alkali-resistant concrete according to claim 8, characterized in that: The mass ratio of water to gelling material is (1-2):(3-4).